1999
DOI: 10.1007/s11661-999-0301-8
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Mg on the microstructure and mechanical behavior of Al-Si-Mg casting alloys

Abstract: The microstructure and tensile behavior of two Al-7 pct Si-Mg casting alloys, with magnesium contents of 0.4 and 0.7 pct, have been studied. Different microstructures were produced by varying the solidification rate and by modification with strontium. An extraction technique was used to determine the maximum size of the eutectic silicon flakes and particles. The eutectic Si particles in the unmodified alloys and, to a lesser extent, in the Sr-modified alloys are larger in the alloys with higher Mg content. Lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
101
1
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 157 publications
(108 citation statements)
references
References 22 publications
4
101
1
2
Order By: Relevance
“…casting. 5 In their study of the effects of Mg, Fe, and solidification rate on the fracture toughness of Al-7Si-xMg-yFe, Murali et al 44 observed that, at 0.2 wt% Fe for all the solidification rates studied, increasing the Mg content from 0.32 to 0.65 wt% causes a reduction in the total impact energy by about 50%. This reduction in the impact energy was attributed to the presence of the coarse ^-phase in the microstructure which acts as a stress raiser and facilitates crack nucleation and propagation.…”
Section: Magnesium Contentmentioning
confidence: 99%
See 3 more Smart Citations
“…casting. 5 In their study of the effects of Mg, Fe, and solidification rate on the fracture toughness of Al-7Si-xMg-yFe, Murali et al 44 observed that, at 0.2 wt% Fe for all the solidification rates studied, increasing the Mg content from 0.32 to 0.65 wt% causes a reduction in the total impact energy by about 50%. This reduction in the impact energy was attributed to the presence of the coarse ^-phase in the microstructure which acts as a stress raiser and facilitates crack nucleation and propagation.…”
Section: Magnesium Contentmentioning
confidence: 99%
“…Moreover, the volume fraction of the iron-rich intermetallics in such alloys is larger than it is in 356 alloys containing 0.45wt% Mg as a result of the formation of larger amounts of the 7r-AlFeMgSi iron-intermetallic phase. 4 ' 5 The stability of the ;r-phase in 357 alloys after applying the standard heat treatment causes a reduction in the amount of free Mg, found in solid solution, which is available for forming Mg2Si precipitates during the aging step. The strength of this kind of alloy is thus lower than expected, leading to the saturation of the UTS and YS values.…”
Section: Defining the Problemmentioning
confidence: 99%
See 2 more Smart Citations
“…The microstructure is shown in Fig.1 and has been described previously [7]. It is highly nonuniform, comprising coarse dendrite colonies (grains) some 0.8 mm in diameter, dendrites with a secondary dendrite arm spacing of ~60 µm, and inter-dendritic eutectic Si inclusions with a volumeequivalent diameter ~3 µm and an aspect ratio of ~1.6 [8] together with age-hardening nanoprecipitates of MgSi.…”
Section: Sample and Materialsmentioning
confidence: 78%